Effect of nitrogen on wheat after different crop sequences - Pöttker, Delmar; Scherer Roman, Erivelton (Pesquisa Agropecuaria Brasileira, 1998)
The great majority of the research reported in the literature about the response of wheat (Triticum aestivum L.) to nitrogen (N) was carried out in soils where the previous crop was soybean (Glycine max L.), which can contribute positively, in terms of N, for the following crop. The need to give farmers that grow wheat after corn (Zea mays L.) new information about N management led us to carry out this research, with the following objectives: a) to evaluate the response of wheat to N when grown after corn; b) to determine the effects of different crops, grown the year before, on the wheat crop; and c) to evaluate if there is a residual effect of N levels applied to the previous corn crop. The response of wheat to nitrogen was assessed after four different crop sequences, which had fallow, oats (Avena strigosa Schieb), chickling pea (Lathyrus sativus L.), and common vetch (Vicia sativa L.) as the preceding winter crops and corn as the summer crop. The crop sequences were the treatments and four levels of nitrogen (0, 25, 65 and 145 kg/ha), topdressed on the wheat crop, formed the subtreatments of the split plot arrangement. The experimental design consisted of completely randomized blocks, with four replications. It was estimated that to achieve maximum yields the wheat (cv. BR 23) would need 110 kg/ha of N after the sequence oats/corn, 100 kg/ha of N after fallow/corn and 97 and 89 kg/ha of N after the sequences chickling pea/corn and common vetch/corn, respectively. There was no effect of the preceding winter crops on the wheat crop. No residual effect of the nitrogen levels applied on corn was observed on wheat.